The Value for the Consumer in Retail - Beatriz Cavalcante Chamie; Ana Akemi Ikeda (BBR: Brazilian Business Review)
Shopping is not just a rational act, but also emotional, involving desire and pleasure. Therefore, retailers need to invest in actions, which create customer value, making the purchase an engaging time. The article’s objective is to understand what the shoppers, the role played by a person during the shopping process, value during the purchasing experience. The research used the meanend chains theory and the laddering technique to identify the formative value elements in a toy store. As a result, it contacted that to create value, the store should offer stimuli to assist children education, a magical and playful atmosphere, a variety that can awaken the child's desire, and foster a sense of a good purchase and the maximization of resources such as time and money. This research increases understanding, from the customer's perspective, of what is valued in a holistic shopping experience.